Experimental Investigation of Graphene Derivatives Based Moisture Sensor Transfer Characteristics for Agriculture Applications - Ukani, Neema Amish; Khera, Shelej; Chakole, Saurabh S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In this work, we have fabricated the sensor to detect the water content in the soil using two graphene derivatives as the sensing material. In this work, we have considered two different graphene derivatives viz “graphene oxide” (GO) and reduced “graphene oxide” (rGO) with three different concentration i.e 0.1 mg, 1 mg and 10 mg dispersed in the 1 ml ethanol, which illustrates the novelty of this work. Further, we have fabricated the interdigitated electrodes (IDEs) on the printed circuit board (PCB), where the aforementioned concentration is drop casted. Further, we studied the sensor transfer characteristics such as the sensitivity, selectivity, hysteresis and stability. From the experimental investigation we have found that 1 mg/1ml (ethanol) concentration outperform when compared with 0.1 mg/1ml (ethanol) and 10 mg/1ml (ethanol) for the both the graphene derivatives used in this work.